COMPREHENSIVE STUDY ON SYNDICATED LOANS: CONCEPTS, MECHANISMS, AND LEGAL IMPLICATIONS IN THE INDONESIAN BANKING INDUSTRY - Sendi Sanjaya; Gunawan Widjaja (Adisam Publisher, 2025)
This study comprehensively examines the concept, mechanism, and legal implications of syndicated loans in the Indonesian banking industry, which are defined as joint loans by a group of banks to a single debtor with uniform terms to overcome the maximum credit limit (BMPK) in accordance with regulations issued by the Financial Services Authority (OJK) and Bank Indonesia (BI), as stipulated in BI Circular Letter Number 6/33/UPK/1973, SEBI 11/26/UPK/1979, PBI 7/14/PBI/2005, and Article 1320 of the Civil Code concerning the validity of agreements. The implementation mechanism includes a sourcing stage with a feasibility study based on 5C analysis, structuring termsheets including covenants such as DSCR >1.2x, selling through syndication roadshows, and servicing by agent banks with a single facility agreement that ensures pro-rata non-joint and several risk sharing. The legal implications emphasise the rights and obligations of the parties involved, such as the debtor in relation to events of default, the lead arranger in relation to fiduciary duty, and the participants through majority voting for debt acceleration or execution of collateral rights in accordance with Law No. 4/1996, with potential disputes resolved based on pacta sunt servanda Article 1338 of the Civil Code.